NASEHAT TENTANG KEKUATIRAN STUDI EKSEGETIS MATIUS 6:25-34 DAN REFLEKSINYA PADA KEHIDUPAN UMAT KRISTEN MASA KINI - Kerdi Bancin (IAKN Tarutung, 2020)
The purpose of this study is to find out what advice about anxiety is based on the book of Matthew 6: 25-34 and to explore the advice about concerns and to reflect it on today's Christians. The research method in writing this scientific paper is a qualitative method with an exegetical study approach. The interpretation method used is the terms and steps of biblical interpretation, so the steps used by researchers are as follows: book recognition, text analysis, textual criticism by comparing opinions of experts and analyzing them, comparison of translations, general context and specific context, general context, special context, form criticism, literary criticism, sitz im leben, verse by verse interpretation, overall interpretation and the scope. As a result of the exegetical study of Matthew 6: 25-34, concerns in the lives of Christians is a teaching of Jesus to strengthen the belief of Christians to put their hope in Jesus.Worry only exists in people who do not know God, and people who often feel anxious are grouped in people who lack faith and belief that God is the only helper and the way of salvation. God has provided everything for humans and humans do not need to think about what will happen tomorrow, but Christians must adopt a good lifestyle every day and they need not think or worry about an uncertain future. Because tomorrow has its own prosperity and only God knows what will happen tomorrow. Jesus wants Christians to seek God's kingdom and God's truth, which means to be obedient and faithful to God. If Christians have sought the kingdom of God, God will provide what is needed by His people. Keyword : Worry